(untitled) (Journal of EAHIL, 2017)
According to the Bethesda Statement on Open Access Policy for libraries and the recommendations of the BOAI10, libraries and librarians have an important role to fulfil in the encouragement of open access. Taking into account the Competencies for Information Professionals of the 21st Century, elaborated by the Special Libraries Association, and the Librarians’ Competencies Profile for Scholarly Publishing and Open Access, we shall identify the competencies and new areas of knowledge and expertise that have been involved in the process of the development and upkeep of our institutional repository (Repositorio SSPA).